There is no fuzziness when it comes to measuring service quality in national parks. (December 2016) - Saayman, Melville; Martín, Juan Carlos; Román, Concepción
Nature-based tourism is the leitmotiv for South African National Parks (SANParks) and Kruger National Park is an icon within the system. The mission and vision of SANParks have evolved from pure conservationism to a more recreation- and customer-oriented agent. The aim of this article is to address the issue of service quality (SQ) provided to satisfy the visitors' needs, demands and expectations. A questionnaire with eight different dimensions and 31 SQ attributes is used to evaluate the SQ for the period April 2012 to March 2013. A method based on a fuzzy multi-criteria decision-making model is applied to dynamically evaluate the SQ in the park. Our results suggest that the SQ differs depending on which time of the year the park is visited, opening an important venue to park managers about whether a price discrimination policy could moderate this observed effect.